Environmental regulation and its influence on energy-environmental performance: Evidence on the Porter Hypothesis from China's iron and steel industry - Wu, Rongxin; Lin, Boqiang (Resources, conservation and recycling, 2022)
•We verify the Porter Hypothesis in the context of China's iron and steel industry.•The U-shaped relationship exists between environmental regulation and efficiency.•Environmental regulation influences efficiency performance by technical innovation.•The impact of environmental regulation on efficiency shows regional heterogeneity.•Future policies for improved efficiency performance are suggested based on results. Environmental regulation is a critical instrument for achieving sustainable economic and social development in the context of carbon neutrality. The iron and steel industry is highly polluting and energy-consuming, posing a significant threat to China's environmental sustainability. Based on the panel of Chinese provincial-level data from 2000 to 2017, this paper empirically examines how environmental regulation affects the iron and steel industry's green development. The findings show that there is a U-shaped relationship between environmental regulation and energy-environmental performance. Low environmental regulation intensity inhibits the improvement of energy-environmental performance. But as the regulation intensity increases, it contributes to the advancement of energy-environmental performance. Environmental regulation affects the industrial energy-environment performance through technological innovation, and the relationship between environmental regulation and technological innovation presents a U-shaped relationship. There are noticeable regional differences in the impact of environmental regulation on energy-environmental performance. The findings provide new evidence to confirm the Porter Hypothesis. Finally, this paper provides policy suggestions for further energy-environmental performance improvements in China's iron and steel industry.